Use of methods for decision-making support in anti-terrorism operations - Wesselényi, Jozef; Kompan, Jaroslav (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
There are not any predefined common military planning processes of military antiterrorism operations at the tactical level within NATO member states. Each country defines its own planning and decision making processes mainly based on the allied publications AJP-5 and COPD. Despite the fact that each country phases the military planning process according to its own procedures and also names each phase differently, there is almost the same background philosophy. Strict definition combined with simpler phases alternation of more complicated tasks with simpler tasks of the military planning process within NATO member states will speed up the military planning process. This thesis describes the military planning process, its tools and common methods used during the decision making process with the main emphasis on the evaluation of the current status. The main goal of this thesis is to propose a new method for the Matrix of Criteria, its test by experiment and integration and incorporation into common military processes. Also, the goal of this thesis is to use this Matrix of Criteria during the military planning process, especially during the course of action comparison, evaluation, and approval step which will make this step simpler and also will focus the attention and the effort of each evaluator staff officer closer to their professional military branch.
Keywords: proces planowania i podejmowania decyzji; planowanie operacji; podejmowanie decyzji; poziom taktyczny; podejmowanie decyzji zarządczych